Editorial - Mujanović, Eldan (Kriminalističke teme, 2015)
Dear reader, In this English edition of the Criminal Justice Issues – the Journal of Criminal justice and Security we are introducing you three new scientific papers that discuss actual problems in the field of criminal investigation science, criminology, criminal law and psychiatry, as well as one conference review. The first of the mentioned papers is original scientific paper titled Prevalence of Recreational Drug Use Among Students of the University of Sarajevo whose intention is to report the characteristics and main consumption patterns of recreational drug use among students of the University of Sarajevo, and this issue is observed through the prism of the “normalization thesis” of drug consumption. On the other side, the author of the review paper titled Assessment of Compliance of the Criminal Codes in Bosnia and Herzegovina with the Council of Europe Cybercrime Convention tends to evaluate (in)directly applicable legislation in Bosnia and Herzegovina regarding cybercrime as one of the most dangerous and the fastest growing criminal activities in the contemporary world. The next review paper titled Assessment and Treatment of War Trauma considers the issue of establishing methodology for estimating the presence of War trauma in post-conflict societies, such as in Bosnia and Herzegovina, Croatia, Serbia, Kosovo or Macedonia. Finally, in accordance with established practice in recent years, the last part of this edition is reserved for professional papers and reviews of students of postgraduate and doctoral studies, so this time we introduce you review of the 15th European Society of Criminology (ESC) conference in perspective of ESC fellowship recipient. At the end, I want to emphasise that preparation and publishing of this edition of the Criminal Justice Issues would not be possible without the support of Mr Andy Aydin-Aitchison, PhD. Also, I would like to express my gratitude to Editorial Board members and peer reviewers who have significantly contributed to the quality of this edition.